A Solar Transistor and Photoferroelectric Memory. (28th February 2018) - Pérez‐Tomás, Amador; Lima, Anderson; Billon, Quentin; Shirley, Ian; Catalan, Gustau; Lira‐Cantú, Mónica
Abstract: This study presents a new self‐powered electronic transistor concept "the solar transistor." The transistor effect is enabled by the functional integration of a ferroelectric‐oxide thin film and an organic bulk heterojunction. The organic heterojunction efficiently harvests photon energy and splits photogenerated excitons into free electron and holes, and the ferroelectric film acts as a switchable electron transport layer with tuneable conduction band offsets that depend on its polarization state. This results in the device photoconductivity modulation. All this (i.e., carrier extraction and poling) is achieved with only two sandwiched electrodes and therefore, with the role of the gating electrode being taken by light. The two‐terminal solar‐powered phototransistor (or solaristor) thus has the added advantages of a compact photodiode architecture in addition to the nonvolatile functionality of a ferroelectric memory that is written by voltage and nondestructively read by light. Abstract : This study presents a new self‐powered electronic device "the solar transistor" . Transistors require an external voltage source and a third terminal known as gate. Solar cells in contrast have only two electrodes but do not have switch. The new ferroelectric‐organic "solaristor" device concept merges in two‐electrode geometry a non‐volatile transistor modulation and the autonomy of solar cells.